The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1159/000320232
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Intravenous Immunoglobulins in Belgium

Abstract: Background: In light of the limited supply of intravenous immunoglobulins, it is important to strive for their appropriate use. Off-label use needs to be discouraged because of the limited supply of intravenous immunoglobulins, their unproven effectiveness in many conditions, their high costs, and the risk of adverse effects. This study aims to document the use of intravenous immunoglobulins in registered and off-label conditions in Belgian hospitals. Methods: Data were derived from the IMS Health hospital dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In 2007, IGs administered in Belgian hospitals constituted 17% of hospital drug expenditure where 50%–60% of the IG use was associated with approved indications and 40%–50% was off‐label, occurring in unspecified conditions (surgery, orthopaedics and oncology). The study demonstrated a rapid change in indication for investigational IG use, which may account for the high percentage of ‘off‐label’ use and poor documentation on the decision process for compassionate use and obtaining informed consent [24]. Computerized decision support for IG prescriptions showed 74 unique indications included in the final list of appropriate use and the appropriate dosages for each indication were programmed into the final order set, allowing a reduction in dose deviation [25].…”
Section: Supply and Use Of Immunoglobulins In Times Of Crisesmentioning
confidence: 99%
“…In 2007, IGs administered in Belgian hospitals constituted 17% of hospital drug expenditure where 50%–60% of the IG use was associated with approved indications and 40%–50% was off‐label, occurring in unspecified conditions (surgery, orthopaedics and oncology). The study demonstrated a rapid change in indication for investigational IG use, which may account for the high percentage of ‘off‐label’ use and poor documentation on the decision process for compassionate use and obtaining informed consent [24]. Computerized decision support for IG prescriptions showed 74 unique indications included in the final list of appropriate use and the appropriate dosages for each indication were programmed into the final order set, allowing a reduction in dose deviation [25].…”
Section: Supply and Use Of Immunoglobulins In Times Of Crisesmentioning
confidence: 99%
“…Given all aforementioned uncertainties, the 15.4% off-label use should be taken as an approximation. A Belgian study in the hospital setting linked off-label use to around 40-50% of all Ig patients in the year 2007, although its methodological limitations, recognized by the author, may have resulted in an overestimation [18].…”
Section: Off-label Usementioning
confidence: 99%
“…An analysis of Ig reimbursement data in Belgian hospitals calculated a total annual Ig product cost of €33.5 million across approved conditions and off-label indications in 9,629 patients, which accounted for 17 percent of total hospital drug expenditure. The Ig treatment of 1,494 patients with secondary immunodeficiency or bone marrow transplantation amounted to €4 million (16). In France, the annual mean cost of Ig treatment per patient with secondary immunodeficiency has been estimated at over €20,000, of which €9,800 were Ig product costs and the remainder were hospital admission costs for Ig infusions and infections (17).…”
Section: Introductionmentioning
confidence: 99%